Primary leiomyosarcoma of the uterine cervix: report of 4 cases, systematic review, and meta-analysis. Issue 5 (October 2020) - Kiliç, Cigdem; Yuksel, Dilek; Cakir, Caner; Turkmen, Osman; Kimyon Comert, Gunsu; Başaran, Derman; Turan, Taner
Background: Primary cervical leiomyosarcomas (CLMS) constitute 21% of all cervical sarcomas. Because of their rarity, to our knowledge, fewer than 40 cases have been reported. The aim of this study is to evaluate the clinical and surgical–pathological features, prognosis, treatment options, and survival of primary CLMS. Methods: A systematic review of the medical literature was conducted to evaluate articles about primary CLMS. The literature was searched between 1959 and May 2019. On final evaluation, there were 29 articles (one consisted of 8 cases; one consisted of 3 cases) and 42 cases with the addition of our 4 cases. Results: Age (⩾48 versus ⩽47 years) (hazard ratio.HR], 4.528; 95% confidence interval.CI], 1.550–13.227; p =0.006) and mitoses count (<10/10 high-power field [HPF] versus ⩾10/10 HPF) (HR, 3.865; 95% CI, 1.046–14.278; p =0.043) are independent prognostic factors for recurrence and age (HR, 5.318; 95% CI, 1.671–16.920; p =0.005) and hysterectomy (performed versus not performed) (HR, 4.377; 95% CI, 1.341–14.283; p =0.014) are independent prognostic factors for death because of disease on multivariate analysis. Conclusions: Information on primary CLMS is sparse and obtained from rare case reports and case series. Hysterectomy must be the first choice of treatment in these patients according to our results on multivariate analysis. The type of hysterectomy does not have an effect on oncologic outcome. Radical hysterectomy is not obligatory and more data are needed to make more accurate conclusions.